Mineral Constituents of Foliage of Sal (Shorea robusta), of Different Quality Classes - Bhatnagar, H. P. (Indian Forester, 1957)
On critically examining the foliar analysis data for different quality classes it is clear that there are significant differences in the amount of different minerals present in the foliage of sal trees of different quality classes. First quality trees show the lowest concentration of minerals in all cases and fourth (i.e. the poorest) quality trees contain the highest amounts of Nitrogen, Potassium and Phosphorous. Calcium and Magnesium are highest in the third quality although in the fourth quality they are almost as high. It seems possible to distinguish various qualities of sal trees on the basis of foliar mineral constituents or in other words the quality of the site is consistently reflected in the foliar composition.